An Exploration of Foreign Language Anxiety and Its Effect to Reading Comprehension - Indrayani Winingsih; Fauzul Etfita; Sri Wahyuni; Arimuliani Ahmad (Universitas Pahlawan Tuanku Tambusai, 2021)
Foreign language anxiety commonly appears in reading, it causes the brain to engaged with unpleasant feelings that it become difficult to seize new information. Thus, this research aimed to classify the levels of students’ reading anxiety and to find the significant difference in reading comprehension between students with higher level of reading anxiety and lower level of reading anxiety. A descriptive design was employed to conduct this research. The data were collected from the first-year students of English Language Education at a Private University in Riau using adapted Questionnaires from Foreign Language Reading Anxiety Inventory (EFLRAI). The result of this research revealed that 8 or 14% of the students are categorize as low anxious level, then 39 or 66% of the students are categorize as medium anxious level and 12 or 20% of them are classified as high anxious level. Furthermore, according to the results of the Mann-Whitney U Test analysis, it figured out that students with lower levels of anxiety outperform the students with higher levels of anxiety in terms of reading comprehension, with a p value of 0.011.